INOVASI KURIKULUM OBE MELALUI PENERAPAN MODEL PROJECT BASED LEARNING BERBASIS DESIGN THINKING TERHADAP KETERAMPILAN MENULIS KARYA ILMIAH MAHASISWA - Siti Raihan; Ratih Utami Ramadhaniati; Faisal Salim; Saprizal Saprizal (CENDEKIA PENDIDIKAN, 2026)
This study aimed to: (1) describe the implementation of the Design Thinking-based Project Based Learning (PjBL) model; (2) describe students' scientific writing skills before and after the implementation; and (3) determine the effect of OBE curriculum innovation through this model on scientific writing skills. The research employed a quantitative approach with a one-group pretest-posttest design. Subjects were elementary school teacher education students at Universitas Negeri Makassar enrolled in a Scientific Writing course, selected through purposive sampling. The instrument was a validated scientific writing skills rubric with high reliability. Data were analyzed using descriptive statistics, paired sample t-test, and N-Gain. The results showed: (1) model implementation through five phases (empathy, define, ideate, prototype, test) achieved an excellent implementation rate; (2) students' scientific writing skills improved from the low category with no students passing to the high category with all students passing; (3) there was a significant effect with improvement in the medium category. The highest improvement occurred in writing mechanics, approaching the high category, while the lowest improvement was in language skills. This study concludes that OBE curriculum innovation through the Design Thinking-based PjBL model has a significant and moderately effective impact on improving students' scientific writing skills.